2003
DOI: 10.1002/j.1939-4640.2003.tb03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Seminal Plasma Motility Inhibitor/Semenogelin in Human Seminal Plasma

Abstract: Semenogelin I and II (Sg I and II) are the major components of human semen coagulum. The protein is rapidly cleaved after ejaculation by the chymotrypsin-like protease prostate-specific antigen (PSA), which results in the liquefaction of the semen coagulum and the progressive release of motile spermatozoa. One of the cleavage products of the protein, a 14-kDa protein, is a sperm motility inhibitor (seminal plasma motility inhibitor [SPMI]). We developed a monoclonal antibody (mAb) that is specific to the fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 26 publications
2
29
0
1
Order By: Relevance
“…In addition, broad bands, characteristic of proteins, have also been observed throughout the entire spectrum, the assignment of which is hindered due to broadening. In view of the abundance of proteins such as semenogelin (Sg), PSA and albumin [3,52], it is possible that few of the peaks observed in the spectra of the present study originate and correspond to resonances from these proteins.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, broad bands, characteristic of proteins, have also been observed throughout the entire spectrum, the assignment of which is hindered due to broadening. In view of the abundance of proteins such as semenogelin (Sg), PSA and albumin [3,52], it is possible that few of the peaks observed in the spectra of the present study originate and correspond to resonances from these proteins.…”
Section: Resultsmentioning
confidence: 91%
“…Notably, semenogelin has been shown to increase in asthenozoospermic samples, which was in good agreement with our present proteomic results. Yoshida et al 52 demonstrated that a 14 kDa fragment of semenogelin has an inhibitory effect on ejaculated spermatozoa. Overall, proteomic analysis techniques were a valuable tool for identifying semenogelin as a sperm motility inhibitor.…”
Section: Functional Proteomics Of a Human Model Of Abnormal Spermatogmentioning
confidence: 99%
“…The testicular volume was evaluated using a punched-out orchidometer. An aliquot of the washed sperm was incubated with 1 g/ml anti-SPMI mouse IgG recognizing SPMI region (monoclonal antibody, before mentioned as anti-Sg antibody, F11) [21] or normal mouse IgG (DAKO Japan, Tokyo, Japan) at 37 ° C for 1 h. Sperm were then washed twice with HBS at 3,300 g for 10 min at 25 ° C. Washed sperm were incubated with Alexa 488-conjugated anti-mouse immunoglobulin G (IgG) (Molecular Probes, Oreg., USA) at 37 ° C for 1 h. The samples were then analyzed using a flow cytometer. Fluorescent staining of sperm was monitored and photographed using an Olympus BX50 epifluorescent microscope equipped with a fluorescein isothiocyanate filter set (Olympus, Tokyo, Japan)…”
Section: Semen Analysis and Hormone Measurementsmentioning
confidence: 99%
“…Previously, we revealed that the SPMI/Sg content of seminal plasma was negatively correlated with sperm motility in normal subjects [21] . However, the correlation was weak, and preliminary measurement of the SPMI contents in the seminal plasma of infertile patients showed no significant correlation with sperm motility.…”
Section: Introductionmentioning
confidence: 99%